THE EFFECT OF RECIPROCAL TEACHING MODEL ON STUDENTS’ READING COMPREHENSION OF DISCUSSION TEXT (A STUDY AT THE XII GRADE SMA NEGERI 1 PINANGSORI IN 2016/2017 ACADEMIC YEAR) - Asriani Hasibuan; Gilbert Simbolon (Universitas Potensi Utama, 2018)
This research aims to find out whether there is any significant effect of reciprocal teaching model on students’ reading comprehension of discussion text a study at the twelfth grade students of SMA Negeri 1 Pinangsori. The researcher take one class of population with cluster sampling, they are XII-IPA 1 there are 36 students. The researcher used experimental method in this research. To get an accurate data, researcher collects data by doing observation and test. After calculating the data, It is found that 1) the result using reciprocal teaching model get the mean score 85,71 it is categorized “very good”, 2) The score of the students’ reading comprehension discussion text before given reciprocal teaching model get the mean score is 62.75 it is categorized “enough”. 3) The score of the students’ reading comprehension discussion text after given reciprocal teaching model get the mean score is 74.19 it is categorized “good”. As a result, the researcher found that value of ttest is 11, 18 then the the researcher found the value of ttable is 1, 29 at 95% significant level. After comparing ttest and ttable, it is got that ttest is greater than ttable (11,18 > 1,29). It means that there is significant effect of Reciprocal Teaching Model on Students’ Reading Comprehension of Discussion Text at the Twelfth grade of SMA Negeri1Pinangsori. The hypothesis is accepted.